Workplace spirituality and organizational citizenship behaviour: Exploring gender as a moderator - A. M. Nasurdin; M. Nejati; Y. K. Mei (South African Journal of Business Management, 2013)
Despite extensive studies on the antecedents of organizational citizenship behaviour (OCB), empirical studies on the effect of the workplace spirituality on OCB remains limited. The present study investigates the effects of workplace spirituality dimensions on OCB, with the moderating role of gender. Analyses of 171 academic staff attached to 15 private institutions of higher learning in Malaysia partially supported the relationship between workplace spirituality and OCB, as well as gender's role as a moderator in the workplace spirituality-OCB linkage. Findings are discussed in the light of available literature. Implications for future research and practice are also highlighted.
Keywords: 650